EFEKTIFITAS EARLY CPAP TERHADAP PERBAIKAN DOWN SCORE BAYI PREMATUR USIA GESTASI 32 MINGGU YANG LAHIR DI RSUD DENGAN LAHIR RUJUKAN DI RUANG NEONATUS RSUD DR.HARYOTO LUMAJANG - Rizqi Naimatul Fitriana; Alwin Widhiyanto; Nafolion Nur Rahmat (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Prematur babies are one of the causes of infant mortality, especially in the first month of life. The incidence of prematurity in pregnancy is caused by multifactors, namely maternal factors, fetal factors, and other factors. The purpose of this study was to determine the effectiveness of Early CPAP on Down Score Improvement for Prematur Babies at 32 Weeks Gestational Age in the Neonate Room who were born at RSUD with referral births at RSUD Dr. HaryotoLumajang. In this study, a pre-experimental research design was used with a one group pretest posttest design approach. The study population was 32 weeks' gestational prematur infants who were born in RSUD with referral births in the neonatal room at RSUD Dr. HaryotoLumajang as many as 22 samples. The sampling technique used purposive sampling. Data collection used Observation Sheets and patient medical record data, for data analysis using the T-Test. This research was conducted from March 12 2023 to April 12 2023. The results showed that those who received CPAP treatment earlier had a better mean score of 4.36 compared to those who received CPAP late, which was 6.18. Early administration of CPAP is effective in improving the Down Score of prematur babies born at 32 weeks' gestation at RSUD dr. Haryoto Lumajang with a value of p = 0.00 <0.05. From this research it is suggested that health services become a source of information for health agencies and recommendations for policy makers to take strategic steps to deal with prematur babies.